Quantifying Ozone-Dependent Emissions of Volatile Organic Compounds from the Human Body - Qu, Y.; Zou, Z.; Weschler, C. J.; Y. Liu; Yang, X. (Environmental Science & Technology, 2023)
Ozone reactions on human body surfaces produce volatile organic compounds (VOCs) that influence indoor air quality. However, the dependence of VOC emissions on the ozone concentration has received limited attention. In this study, we conducted 36 sets of single-person chamber experiments with three volunteers exposed to ozone concentrations ranging from 0 to 32 ppb. Emission fluxes from human body surfaces were measured for 11 targeted skin-oil oxidation products. For the majority of these products, the emission fluxes linearly correlated with ozone concentration, indicating a constant surface yield (moles of VOC emitted per mole of ozone deposited). However, for the second-generation oxidation product 4-oxopentanal, a higher surface yield was observed at higher ozone concentrations. Furthermore, many VOCs have substantial emissions in the absence of ozone. Overall, these results suggest that the complex surface reactions and mass transfer processes involved in ozone-dependent VOC emissions from the human body can be represented using a simplified parametrization based on surface yield and baseline emission flux. Values of these two parameters were quantified for targeted products and estimated for other semiquantified VOC signals, facilitating the inclusion of ozone/skin oil chemistry in indoor air quality models and providing new insights on skin oil chemistry.